Actomyosin bundles serve as a tension sensor and a platform for ERK activation - Hirata, Hiroaki (EMBO Rep, 2015)
Tensile forces generated by stress fibers drive signal transduction events at focal adhesions. Here, we report that stress fibers per se act as a platform for tension-induced activation of biochemical signals. The MAP kinase, ERK is activated on stress fibers in a myosin II-dependent manner. In myosin II-inhibited cells, uniaxial stretching of cell adhesion substrates restores ERK activation on stress fibers. By quantifying myosin II- or mechanical stretch-mediated tensile forces in individual stress fibers, we show that ERK activation on stress fibers correlates positively with tensile forces acting on the fibers, indicating stress fibers as a tension sensor in ERK activation. Myosin II-dependent ERK activation is also observed on actomyosin bundles connecting E-cadherin clusters, thus suggesting that actomyosin bundles, in general, work as a platform for tension-dependent ERK activation.